Minimally Important Difference in the Foot and Ankle Outcome Score Among Patients Undergoing Hallux Valgus Surgery. (June 2019) - Desai, Sameer; Peterson, Alexander C.; Wing, Kevin; Younger, Alastair; Crump, Trafford; Liu, Guiping; Veljkovic, Andrea; Penner, Murray; Sutherland, Jason M.
Background: Patient-reported outcomes are increasingly used as measures of effectiveness of interventions. To make the tools more useful, therapeutic thresholds known as minimally important differences have been developed. The objective of this study was to calculate minimally important differences for the domains of the Foot and Ankle Outcome Score for hallux valgus surgery. Methods: The study was based on a retrospective analysis of patients newly scheduled for bunion correction surgery and completing patient-reported outcomes between October 2013 and January 2018. This study used anchor- and distribution-based approaches to calculate the minimally important difference for the instrument's 5 domains. Confidence intervals were calculated for each approach. There were 91 participants included in the study. Results: Using anchor- and distribution-based approaches, the minimally important difference for the pain domain ranged from 5.8 to 10.2, from 0.3 to 6.9 for the symptoms domain, 8.3 to 10.3 for the activities of daily living domain, 7.4 to 11.1 for the quality of life domain, and from 7.0 to 15.7 for the sports and recreation domain. Small differences in the activities of daily living domain may be more clinically important for patients with better function. Discussion: The range of minimally important difference values for each domain indicate how the Foot and Ankle Outcome Score corresponded to bunion correction surgery. The sports and recreation domain showed considerable variability in the range of values and may be associated with the domain's lack of responsiveness. Overall, most minimally important difference values for the domains of FAOS ranged from above 4 to below 16. Level of Evidence: Level III, retrospective comparative series.